Effect of Subacromial Injections of Hyaluronan on Different Grades of Rotator Cuff Lesion: A Prospective Study. (September 2013) - Gigante, A.; Cecconi, S.; Enea, D.; Cesari, E.; Valeri, G.; Busilacchi, A.
Rotator cuff lesions are quite common and in some cases Hyaluronic Acid (HA) can play a role in pain relief and in restoring functions. The aim of the study was to point out the correct indications for HA injection therapy through a prospective study: firstly defining the safety and efficacy of HA in the different grades of cuff tears, then evaluating the maintenance at 90 days, as secondary endpoint. A prospective, open-label uncontrolled study was developed. One hundred patients diagnosed with different rotator cuff lesions were divided into 4 grade-related groups based on a modified Neer's classification. A cycle of 3 US-guided injections of medium-low weight HA was performed through the anterolateral way, one every two weeks. Follow-up was at 0, 15, 30, 45 and 90 days. VAS, Oxford-Shoulder-Score (OSS) and Constant-Murley were used for evaluations. In grade I and II, at day 45, a significant reduction of VAS and increase of Constant-Murley and OSS resulted. In grade IV VAS slowly decreased in the first 45 days, while OSS and Constant did not improve significantly. In grade III patients had no benefit from a clinical and subjective point of view. At ninety days the beneficial effect was still maintained in grades I, II and IV. Overall, the treatment showed a high tolerability profile. In conclusion, patients affected by bursitis or partial cuff tears benefit from HA, while in cuff arthropathy HA might only delay surgery or represent a palliative. In complete tears HA was not effective in pain relief or functional recovery.